Socio-demographic and Clinical Profile of Treatment-seeking Drug Abusers Attending a Hospital in South Kashmir: A Cross-sectional Hospital-based Study - Seema Batool Shah; Mansoor Ahmad Dar; Pinki Kumari; Javid Ahmad Shiekh; Zain Bin Mushtaq; Junaid Ahmad Tailie (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Substance abuse is one of the major public health problems in the present world, and so in Kashmir. The geographical location of Kashmir and the prevailing conflict has made the population vulnerable to drug abuse. Data from different areas of Kashmir has pointed out the changing pattern of substance abuse, and the rising trend of opioid use. However, there have been no studies from southern Kashmir. Aim: To study the socio-demographic and clinical profile of treatment-seeking drug abusers attending General Psychiatric Outpatient Department (OPD) at the newly established Government Medical College, Anantnag, Kashmir, India. Materials and Methods: This cross-sectional, hospital-based study was conducted from January 2020 to June 2021. A total of 213 treatment-seeking drug abusers were included in the study. Diagnosis of substance dependence was established by applying the International Classification of Disease version 10. The clinical and socio-demographic variables were studied using a semi-structured proforma, and the variables were presented as frequency and mean. The data were analysed using Epi Info software version 7.0. Results: The mean age of the study population was 23.4 years. Young adults were the most common population using substances. Opioids (25.3%) were the predominantly used drug, although polysubstance formed the majority at 48.8%. More than 60% of patients were intravenous drug users. Peer pressure and curiosity were the most common specified reasons for initiation of substance (47.4% and 12.2%, respectively). More than 50% of cases had past failed attempts at abstinence. Craving was still the most common reason for relapse (42.8%). Conclusion: The present study results reiterate the presence of a hazardous pattern of substance use in the young population. The intravenous drug use and the secondary infections arising out of that are alarming. The results encourage the conduct of large scale community-based studies and robust policy making and law enforcement.